2020
DOI: 10.1007/s13127-020-00462-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomy, phylogeny and biogeography of the Niphargus tatrensis species complex (Amphipoda, Niphargidae) in Austria

Abstract: The Niphargus tatrensis species complex, entirely subterranean, has a wide distribution range extending from Southern Poland to Austria and Slovenia. Because of its large and confusing morphological variability, it was subdivided into several 'forms', four of which described from Austrian caves. To shed light on this chaotic situation, we sampled the type localities of all described species and forms in the complex, as well as additional sites in Austria, and used nuclear (28S, ITS) and mtDNA (COI) sequences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Using the COI mitochondrial marker, estimates vary from 13 to 21, while using the nuclear rDNA ITS region, numbers are quite lower (5-7 species). This discordance is well known in niphargids (Stoch et al 2020), especially in areas affected by glaciations. COI-based oversplitting may be quite common (Després 2019; Stoch et al (2020) as a result of complex demographic history of lineage divergence/fusion during the Pleistocene climatic fluctuations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Using the COI mitochondrial marker, estimates vary from 13 to 21, while using the nuclear rDNA ITS region, numbers are quite lower (5-7 species). This discordance is well known in niphargids (Stoch et al 2020), especially in areas affected by glaciations. COI-based oversplitting may be quite common (Després 2019; Stoch et al (2020) as a result of complex demographic history of lineage divergence/fusion during the Pleistocene climatic fluctuations.…”
Section: Discussionmentioning
confidence: 75%
“…COI-based oversplitting may be quite common (Després 2019; Stoch et al (2020) as a result of complex demographic history of lineage divergence/fusion during the Pleistocene climatic fluctuations. Relying on the fact that most of the recent splits in the Austrian clade of the Niphargus tatrensis complex took place during the Pleistocene, Stoch et al (2020) proposed to accept the species number suggested by the ITS region. However, within the paleogeographic scenario delineated in the Southern Limestone Alps, where most of the splits took place during Miocene and Pleistocene, it is legitimate to raise doubts about the validity of this argument.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent river floods are considered to be the main routes of distribution for epigean species (Copilaș-Ciocianu et al, 2017, 2018, while the distribution of subterranean species is usually associated with ancient fluctuations in the level of the ancient Tethys Sea in Europe, or its later (Miocene) separated basins such as Paratethys etc. (Fišer et al, 2007;Eme et al, 2017;Delić et al, 2017;Stoch et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the behavior of KoT, we reanalyzed the COI dataset from one recent article (Stoch et al, 2020). In this article, a dataset of 34 COI sequences of specimens of the Niphargus tatrensis species complex was analyzed using a diversity of approaches:…”
Section: Biological Examplementioning
confidence: 99%
“…To investigate the behavior of KoT, we reanalyzed the COI dataset from one recent article (Stoch et al, 2020). In this article, a dataset of 34 COI sequences of specimens of the Niphargus tatrensis species complex was analyzed using a diversity of approaches: mPTP Kapli et al (2017) delimited seven putative species, ABGD (Puillandre et al, 2012) returned ten of them, and bPTP (Zhang et al, 2013) and ST-GMYC (Pons et al, 2006) delineated eleven species-level units.…”
Section: Biological Examplementioning
confidence: 99%